Pediatric clinical ophthalmology a color handbook - Olitsky, Scott E.; Nelson, Leonard B. (Color handbook., 2012)
This clinically oriented volume reviews the signs, symptoms and treatment of common ocular diseases and disorders in infants and children. This book is useful for all those who care for affected children, including paediatricians, primary care and emergency physicians, trainee ophthalmologists, optometrists and medical students.